CONTEXTUALISING FORM AND FUNCTION FOR THE SAKE OF THE LEARNERS IN CLT - Fuad Arif Fudyartanto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
Arguments that the ultimate purpose of L2 acquisition and learning isto communicate have been widely accepted. To get a better result, acombination of instruction and opportunities to practice incommunication is necessary. Instruction can provide learners withcommunicative competence, and practice can improve the automaticprocessing of this competence to communicate (Brown, 2001). CLTinstruction should therefore equip L2 learners with both formal andfunctional aspects of the language. Depending on the context of thelearners, focus on form and function are here viewed as a continuumand complementary to each other. By doing so, it is expected that L2learners are well provided with ability to perceive not only the wholepicture (in this case to communicate) but also small pieces (ofgrammar, form). It is believed that SLTL with activities that focus onboth form (grammar) and function (communication) tends to producelearners with greater accuracy and fluency.